Gastrostomy, tracheostomy, opioid, and health care utilization among patients with recurrent/metastatic head and neck cancer receiving immunotherapy. Issue 28 (1st October 2022) - Uy, Natalie F.; Ng, Kevin; Voutsinas, Jenna M.; Wu, Vicky; Futran, Neal D.; Houlton, Jeffrey; Barber, Brittany; Laramore, George E.; Parvathaneni, Upendra; Liao, Jay Justin; Rodriguez, Cristina P.
Abstract : 296 Background: Immune checkpoint inhibitors (ICI) are approved for recurrent and/or metastatic squamous head and neck cancers (R/M HNSCC). Landmark trials have shown stable or improved patient (pt) reported quality of life outcomes. It is unclear how these translate into gastrostomy (G) and tracheostomy (T) dependence, opioid use, or ER/unplanned hospitalizations (UH) in an unselected population. We sought to explore these in our large single institution cohort. Methods: We reviewed R/M HNSCC pts receiving ICI at a tertiary referral NCI designated cancer center. Outcomes were assessed between the first dose of ICI and 100 days after the last dose of ICI. Overall survival (OS) was estimated via Kaplan-Meier estimation. Differences between groups were assessed via log-rank testing procedure and adjusted for age, tumor characteristics, and smoking status. Results: Between 1/2012 and 12/2019, we treated 152 pts with ICI, mostly male (n = 142, 82%), partnered/married (n = 103, 68%), with median age 64 years (range 23 – 90). The most common primary sites were oropharynx (n = 55, 36%) and oral cavity (n = 33, 22%). 50 (35%) had ≥ 2 lines of prior systemic therapy and 29 (19%) had an ECOG ≥ 2. The most common pt races were white (n = 114, 75%), Asian (n = 14, 9%), and Hispanic, any race (n = 6, 4%). 83 (55%) and 23 (15%) had history of smoking and heavy alcohol use respectively. Median duration of ICI therapy was 95 days (range 1-1720). Prior to ICI, 49 (32%) had G, 17 (11%) had T, and 15 (10%) had both. While on ICI, 6 (4%) had G placed, and 1 (1%) had a G removed; 1 (1%) had T placed, and 2 (1%) had T removed. 69 (45%) had ER visits and 57 (38%) had UH; 11 (7%) were directly related to ICI adverse effects. Prior to ICI, 104 (68%) were on opiates; requirements increased in 58 (41%) pts and decreased in 17 (12%) pts. Pre-existing G prior to ICI had worse OS on log-rank testing, but significance was lost when adjusted for variables. Pre-existing T prior to ICI (p = 0.001, HR 3.08, 95% Cl [1.56, 6.08]), and pts with increasing opiate requirements on ICI (p value = 0.0007, HR 2.13, 95% Cl [1.38, 3.28]) had worse OS. Conclusions: In our cohort, ICI did not change G or T usage. Pre-existing T and increasing opiate use were also associated with worse survival. Our data supports augmentation of palliative care and advanced care planning in the R/M HNSCC population.